Diagnóstico da fragmentação florestal na bacia hidrográfica do Rio Paracatu-MG - Lopes, Adrieny Kerollen Alves (2023)
The Paracatu River Basin, located in the Cerrado Biome, has been suffering since the 1970s, with the intense processes of land use conversion, modifying the landscape through intense deforestation. In this sense, forest fragmentation can be studied by Landscape Ecology, through spatial data characterizing current conditions, development, and temporal change of fragments. Here, the main goal is to analyze the spatiotemporal changes in land use over a 30- year horizon and their impacts on the fragmentation of Cerrado vegetation in the Paracatu River Basin in Minas Gerais, Brazil. The Paracatu River Basin (BRP) is an important subbasin of the São Francisco River, located almost entirely in the northwest region of Minas Gerais, with an area of approximately 45,000 km2. For data analysis, data from MapBiomas from the years 1990, 2000, 2010, and 2020 were used. Based on these data, in QGIS version 3.16, the main categories of land use were reclassified into classes: Forest, Natural formation non-forestry, Agriculture, Non-vegetated areas (including mining and urban areas), and Water bodies. From this, through the data from the vector file, it was possible to verify the evolution of the soil cover dynamics over the years. The Semi-Automatic Classification Plugin (SCP) was used to assess the intensity of landscape transitions in the different land cover classes for the studied decades, showing the dynamics of land cover in the BRP. The Forest and NonForest Natural Formation classes were isolated and converted into a single class corresponding to the forest fragments. In order to obtain the number of existing fragments, the size relationship between them, the format, and the degree of connectivity, landscape ecology metrics were applied. Through the results, it was observed that there was a reduction of the class Forest and Non-Forest Natural Vegetation, less 7.1% and 0.9%, respectively, in 30 years analyzed. On the other hand, the Agricultural class increased 8.7% (3,894.8 km2) from 1990 to 2020. This percentage is greater than the decrease of the Forest and Non-Forest Natural Vegetation classes. The SCP analysis showed that during the 30 years of study, only 2,641.77 km2, equivalent to 5.87% of the total area of the BRP, were reforested. While 6,490.38 km2 (14.42% of the total area) were deforested: that is, regions that were previously classified as Forest or Non-Forest Vegetal Formation were transformed into areas of anthropic use (Agriculture, Livestock, Non-vegetated Area). The other 79.71% of the basin area remained unchanged, that is, areas whose uses did not undergo significant changes over the years studied.